2014
DOI: 10.4103/0974-2069.132476
|View full text |Cite
|
Sign up to set email alerts
|

Total anomalous systemic venous drainage to the left atrium: An entity reviewed and investigated

Abstract: We present three unusual cases of total anomalous systemic venous drainage (TASVD) where all the systemic veins were abnormally connected to the atrium that drained into the left ventricle (LV). All three patients had features consistent with left atrial isomerism. Based on the available evidence and review of literature we propose that TASVD be included as a part of the syndrome of left atrial isomerism. A classification for TASVD is also proposed with surgical implications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
28
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(29 citation statements)
references
References 12 publications
1
28
0
Order By: Relevance
“…Other reports suggest that these abnormal veins connect more commonly to the rightsided atrium. [1][2][3][4][5]8,9 Three cases described by Awasthy and colleagues 8 had left isomerism syndrome characteristics, similar to our case. Thus it is justifiable to suggest total anomalous systemic drainage as one of the indicators of left isomerism syndrome.…”
Section: Discussionsupporting
confidence: 90%
“…Other reports suggest that these abnormal veins connect more commonly to the rightsided atrium. [1][2][3][4][5]8,9 Three cases described by Awasthy and colleagues 8 had left isomerism syndrome characteristics, similar to our case. Thus it is justifiable to suggest total anomalous systemic drainage as one of the indicators of left isomerism syndrome.…”
Section: Discussionsupporting
confidence: 90%
“…Most cases of total anomalous systemic venous connection to the left atrium reported in the literature were associated with left isomerism. [5][6][7][8] On surgical inspection of the appendage of the right-sided atrium, we found that it exhibited the anatomical characteristics of a left-atrial appendagenamely, a long narrow chamber with a smooth-looking wall, possibly indicating heterotaxy syndrome with left-atrial isomerism. The chest X-ray, however, did not show bilateral symmetric left bronchi with widened carina as typically observed in left bronchial isomerism.…”
Section: Discussionmentioning
confidence: 86%
“…Among 100 patients with anomalous systemic venous connections undergoing surgery, only 3 patients have a total anomalous systemic venous connection to the left atrium. 2 Only a few cases have been reported thus far, [3][4][5][6][7][8] and the literature on this subject has more of a surgical perspective. Most patients presented later in life, from childhood to adulthood, mainly with cyanosis.…”
Section: Discussionmentioning
confidence: 99%
“…TASVC may also be associated with left or right isomerism. 1,5 Our patient presented with ectopic atrial rhythm and severe pulmonary arterial hypertension, which is unusual in patients with isolated TASVC, although such a presentation is common in TASVC associated with heterotaxy. TASVC was classified by Zhang and colleagues 6 into two types: type 1 with drainage of the IVC to the left atrium, and type 2 with azygos continuation of the IVC.…”
Section: Discussionmentioning
confidence: 89%
“…It is usually associated with heterotaxy syndrome and left isomerism. 1 We describe a case of isolated TASVC without any associated abnormalities.…”
Section: Introductionmentioning
confidence: 97%